Morphology-tuned exceptional catalytic activity of porous-polymer-supported Mn3O4 in aerobic sp3 C-H bond oxidation of aromatic hydrocarbons and alcohols - Mondal, John (2014)
Mn3O4 nanomaterials with different morphologies (sphere, nanowire, and octahedron) embedded into functionalized nanoporous polymers were developed by a facile one-pot solvothermal technique at different temperatures. These Mn3O4-based hybrid materials could behave as heterogeneous nanocatalysts to perform sp3 C[BOND]H bond oxidation of aromatic hydrocarbons and alcohols with molecular oxygen as an economic oxidant. Catalytic activity could be effectively tuned by changing the morphology of incorporated Mn3O4 in nanoporous polymer. These Mn3O4-based hybrid materials exhibited remarkable catalytic performance for sp3 C[BOND]H bond oxidation as compared with bare Mn3O4 nanoparticles. Mn3O4 with octahedral morphology in nanoporous polymer exhibited the highest catalytic activity on account of its more exposed crystallographic planes and edges. These Mn3O4-based nanocatalysts could be recycled and reused for consecutive catalytic cycles without a significant loss of catalytic activity.